The expression of genes that regulat pancreatic beta cell regeneration in neonatal streptozotocin diabetic model - KAYA DAĞISTANLI, Fatma; ÖZTÜRK, Melek (Cerrahpaşa Medical Journal, 2019)
The aims of this study are to determine distribution of gene expression of insulin, pdx-1 and synaptophisin in both intra and extra islet cells, to determine the role of the endocrine cells in the remodelling of islets that was damaged with STZ treatment in the early stages of the neonatal STZ (n-STZ) diabetic model. In this study 8 groups each containing 7 neonatal Wistar albino rats were established. On the second day after birth 100mg/kg STZ (n-STZ) was given four groups. Each group was decapitated on the 3rd, 5th, 7th and 10th day respectively together with the healthy control groups. Pancreas tissue was fixed in % 10 formaline and embedded in paraffin. Digoxigenin labeled insulin was used for in situ hybridization. Insulin, glucagon, somatostatin, synaptophisin and pdx-1 antibodies were used for immunohistochemistry on serial parafine sections. Islet sizes of STZ treated groups were smaller than control groups, while the area containing insulin mRNA signal positive cells in n-STZ diabetic group were smaller than controls. Although pdx-1 immunopositive cells were decreased in STZ diabetic groups compared to control groups. Numerous synaptophysin positive cells were detected in the lining of duct epithelium as well as exocrine tissue in the STZ diabetic groups. Beta cell destrucition was in the highest level in n-STZ 5 days group, and an effective beta cell regeneration occured between 7 th and 10 th day of the experiment. Synapthophysin and pdx-1 may be a useful marker in the detection of precursor cells transforming to β cells.